Design of Early Child Growth Monitoring Media - Sutono, Sutono; Fauzi, Hamdan Daalal; Rahayu, Bety Agustina (CV. Global Health Science Group, 2023)
The golden generation is the successor of the nation. Seeing this, the growth and development of children must be monitored because this monitoring has the aim of finding irregularities early so that treatment can be carried out as soon as possible. Monitoring methods that are easy to carry out with results according to the guidelines are the facilities needed by caregivers. The purpose of this study was to design media for monitoring and development of early childhood at Littlecare PAUD. The action research method is used in this study. Implementation of these solutions is made systematically which includes health services and provides additional education or information. The activity was carried out from December 2022-April 2023. Respondents in this activity consisted of 3 admin teachers and 2 students. In the Design and Development of a Website-Based Child Development Measurement Application for Early Childhood Education in Little Care Yogyakarta, namely using the Software Development Life Cycle (SDLC) method. This new system provides convenience for its users compared to manual monitoring. This application has been designed according to the needs of the school, starting from facilitating the search for student data, knowing the current age, monitoring the growth and development of fine motor, gross motor, language, and socialization according to DDST. This application has also been designed with final conclusions regarding child development. The Little Pedia application that was compiled is stated to be able to help save time, make it easier to find student data when needed, as well as save the budget spent on reporting.